Graying arts access: crafting creative online programming to promote older adults' artistic engagement in and beyond pandemic time - McFarland, Jami; Rice, Carla; Changfoot, Nadine; La Rose, Tara; Alfaro-Laganse, Carmela; Badri, Suad; Smith, Kathy; Katz, Becky (Frontiers in Sociology, 2024)
IntroductionDeclared a global pandemic by the World Health Organization (WHO) in March 2020, the COVID-19 virus and attendant patchwork of local, regional, and national government-initiated public health responses to it unexpectedly opened possibilities for greater access to culture for disabled and chronically ill people in ways that were unimagined in pre-pandemic times. During the “emergency” period of the pandemic, the fields of critical disability studies and aging studies independently demonstrated the importance and value of shifting to digital technologies for disabled people and older adults respectively; however, to date, little scholarship has considered the value of digital technologies for older adults aging with and into disabilities beyond pandemic time.MethodsInformed by the theoretical insights of scholarship exploring critical access and the aging-disability nexus, this paper draws from empirical data collected during Phase 2 of Direct[Message]: Digital Access to Artistic Engagement, a collaborative, community-based, arts-informed research project based in Southwestern Ontario (Canada). Drawing from 50 qualitative interviews with aging adults from un/under/represented communities, findings explore the intersections of older age and disability, including dynamics related to gender, sexuality, migration, size, race/ethnicity, and other differences, as these relate to access to and enjoyment of creative spaces before, during, and “after” the COVID-19 pandemic.ResultsResults show that older adults aging with/into disabilities in Southwestern Ontario express an overwhelming desire and even urgent need to access interactive arts programming from the relatively safe spaces of their homes both within and outside pandemic time.DiscussionAs the normative world pushed for a return to ableist normative life in 2022, a year marked by “severe” rates of the highly infectious Omicron variant and the loss of effective public measures, such as community masking and widely available testing, participants described the need for continued access to creative and social participation via remote options that sidestepped socially exclusive and physically inaccessible spaces. Findings indicate a need for increased investment in digital arts programming for older adults aging with/into disabilities.